2008
DOI: 10.1002/jssc.200700577
|View full text |Cite
|
Sign up to set email alerts
|

Fast‐GC–conventional quadrupole mass spectrometry in essential oil analysis

Abstract: This study reports on the compatibility of a conventional quadrupole MS (qMS) as detector for Fast-GC in terms of separation, identification, and quantitation when applied to the analysis of peppermint essential oil (e.o.), adopted as representative of this field. The influence of Fast-GC carried out on a 10 mx0.1 mm id narrow bore column with temperature programmes from 20 to 60 degrees C/min on the results of a qMS in total ion chromatograms (TIC) at different speeds (from 999 and 11 111 amu/s) and SIM modes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…The mass spectrometric parameters were as follows; low mass 40, high mass 800, MS quad 150 °C, MS source 230 °C. Gas chromatography–mass spectrometry (GC‐MS) enables fast analysis, good separation and reliable quantitative and qualitative data 17…”
Section: Methodsmentioning
confidence: 99%
“…The mass spectrometric parameters were as follows; low mass 40, high mass 800, MS quad 150 °C, MS source 230 °C. Gas chromatography–mass spectrometry (GC‐MS) enables fast analysis, good separation and reliable quantitative and qualitative data 17…”
Section: Methodsmentioning
confidence: 99%
“…suspected allergens in perfumes). The state of the art of the F-GC-qMS combination was exhaustively and critically reviewed by Mastovska et al [35] F-GC-qMS in EO analysis was also recently investigated in depth by Rubiolo et al [36] in a study dealing with separation, identification and quantitation of 10 components characteristic of peppermint EO. They showed that operating at a suitable scan speed in TIC mode (from 999 and 11111 amu/s) or at a suitable dwell time in SIM mode (0.5-100 ms), the results obtained with F-GC-qMS with a 10 m ¥ 0.1 mm i.d.…”
Section: Fast-gc and Fast-gc-qms Eo Analysismentioning
confidence: 99%
“…Nowadays, GC-MS evolves towards speeding up the separation and detection steps, with approaches and instrumentation suitable for reducing the analysis time to a minimum while keeping good separation and producing reliable qualitative and quantitative results. [11] This goal has been achieved with short narrow-bore columns and modern GC instrumentation provided with automatic injectors, electronic flow control, ovens with high precision temperature and temperature rate controls, detectors with high sensitivity, electronic stability (low signal-tonoise ratio) and frequency of signal acquisition. An important contribution to fast GC in routine analysis was the method translation approach introduced by Klee and Blumberg, [12] which makes it possible to find the optimal separation/speed trade-off for a conventional GC method and to derive fast GC conditions from it automatically.…”
Section: Sample Preparationmentioning
confidence: 99%